EKSISTENSI HUKUMAN MATI DALAM DUNIA INTERNASIONAL - , Mujizad Abdurrazak, Drs. Muhadi Sugiono, MA. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The purpose of this thesis is to analyze the existence of the death penalty in international world today which increasingly strengthens the values of human rights as the standard norm in order to maintain and run the activities of international relations each other. It is inevitable that human rights as one of the pillars of the three pillars in the Charter of the United Nations (UN) have had a major impact so significantly on the development of the international world. However, whether the death penalty policy in the countries of the world is also affected by these rights, or in other words whether the death penalty as a legal activity that has been carried out for centuries in nearly all countries in the world will be abandoned along with the more-powerful principle of human rights. In fact, the death penalty is still the policy of the majority of the international community. This indicates that the rights have not fully given effects though it has become the norm of international standard. So what effect has been given by the rights, primarily against the death penalty? It is inevitable that rights recently have become one of the tools to remove the death penalty. Using human rights issues to influence policy makers is a norm that now emerges in international society. Until now, the issues of the death penalty as a form of human rights violations have reached norm cascade and have made several countries abolish the death penalty from its legal policy. Although not all countries do the removal but the direction of removal from year to year has increased significantly. From this, The author concludes that the influence of human rights today merely urged countries to abolish the death penalty and has not reached the stage of a harder (forced) to abandon this sentence. This is caused by three interrelated things, ie: 1) the constitution or supreme legislation and the form of government adopted by a country, 2) the social, political and international law affecting the pattern of thinking and social relations in society, and 3) the relevance of the old values in the development of times which is much more advanced. Key words : Death Penalty, Human Rights.